A broad spectrum of posterior reversible encephalopathy syndrome - a case series with clinical and paraclinical characterisation, and histopathological findings - Ismail, Fatme Seval; van de Nes, Johannes; Kleffner, Ilka (BMC neurology, 2021)
Background Posterior reversible encephalopathy syndrome (PRES) is clinical-neuroradiologically defined and potentially reversible, so there are limited data about histopathological findings. We aimed to describe the clinical and paraclinical features of patients with PRES with regard to its reversibility. Methods This retrospective case series encompasses 15 PRES cases out of 1300 evaluated patients from a single German center between January 1, 2010, and June 15, 2020. PRES was established according to the diagnostic criteria as proposed by the Berlin PRES Study 2012. One of the cases studied was subject to brain autopsy. Results From the 15 patients studied (median age 53 years, range 17-73; 11 female), 67 % presented with epileptic seizures, 40 % suffered from encephalopathy with reduced consciousness and 53 % developed delirium, while 47 % had headache and visual disturbances. Subcortical brain MRI abnormalities related to PRES were observed in all patients. One patient developed spinal ischemia and another Guillain-Barré syndrome in addition to PRES. Hypertensive blood pressure was the main underlying/trigger condition in all patients. Clinical symptoms and MRI changes were not reversible in 42 %, even progressive in 3 out of these 5 patients. Median time from symptom onset to diagnosis in these non-reversible cases was 7 days (range 0-13), while the median delay in diagnosis in the reversible group was 1 day (range 0-3). Cerebellar/brain stem involvement and status epilepticus were more frequently in patients with non-reversible disease course. Mortality due to PRES occurred in 13 % of these patients. Neuropathological examination of the brain of a 57-year-old female patient revealed major leukencephalopathic changes, fibrinoid necrosis of endothelial cells and fresh petechial hemorrhages in accordance with PRES. Conclusions Our case series demonstrates that PRES was not reversible in 42 % of the studied patients. Delay in diagnosis seems to contribute to limited reversibility and poor outcome. Keywords: Posterior reversible encephalopathy syndrome (PRES), Reversibility, Histopathological findings